Konversi Usahatani Karet Menjadi Usahatani Kelapa Sawit Kecamatan Belitang Hilir Kabubaten Sekadau - Herudin Herudin; Erlinda Yurisinthae; Adi Suyatno (Jurnal Sosial Ekonomi Pertanian, 2022)
Agricultural sector is very important in the Indonesian economy, especially the plantation sub-sector, which contributes to GDP (Product Domestic Broto) of 3.30 percent. The purpose of the study was to determine the factors that influence the conversion of rubber farming into oil palm farming. This study uses logit analysis with purposive sampling method, this research was conducted in Belitang Hilir District, Sekadau Regency. The method in this study uses descriptive qualitative analysis by analyzing farmers who convert and those who do not. Respondents in this study consisted of 100 respondents calculated using the Slovin formula with 50 rubber farmers and 50 oil palm farmers assuming 50 oil palm farmers were farmers who converted from rubber to oil palm. The results of this study indicate that the factors that influence farming conversion are education, rubber farming income, and oil palm farming income.